Determinants of Digital Economic Literacy in Economics Education Students in South Tangerang - Ambar Widya Lestari; Citra Eliyani; Purwati Yuni Rahayu (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2026)
This study examines the influence of project-based immersive learning and digital financial experience on the digital economic literacy of Economics Education students in South Tangerang. The research aims to analyze the individual and combined effects of these variables in improving students’ ability to understand, manage, and utilize digital economic technologies effectively. A quantitative survey method was employed. The population consisted of Economics Education students in South Tangerang who had participated in project-based courses and were enrolled in at least the third semester. Using purposive sampling, a minimum of 200 students from Universitas Pamulang were selected as respondents. Data were collected through observations, interviews, and structured questionnaires. The research instruments were tested for validity and reliability before data collection. Furthermore, classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted prior to multiple linear regression analysis. The findings indicate that project-based immersive learning has a positive and significant effect on students’ digital economic literacy. Digital financial experience also positively and significantly contributes to improving digital economic literacy. Students with greater exposure to digital financial services tend to demonstrate higher levels of digital economic literacy. Moreover, the simultaneous influence of project-based immersive learning and digital financial experience significantly enhances students’ digital economic literacy. These findings suggest that integrating project-based learning with practical digital financial experiences can effectively strengthen students’ competencies in navigating the digital economy and adapting to ongoing digital transformation.